PROSES BERPIKIR KOMPUTASIONAL SISWA BERDASARKAN PRIOR KNOWLEDGE - Gunawan Gunawan; Joko Purwanto; Fitrianto Eko Subekti (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Prior knowledge is one of the primary factors in the birth of ideas in computational thinking. Solving problems in the 21st century requires computational thinking skills. The computational thinking process involves abstraction, design, decomposition, algorithms, and verification. Research was conducted to describe students' computational thinking processes in solving contextual problems based on previous knowledge. The research process uses qualitative with an explanatory approach. A total of 40 students were grouped into low, medium, and high prior knowledge categories. One subject was taken in each category using purposive sampling. Tests and interviews were carried out for data collection. Data analysis consists of data reduction, presentation, and conclusions. The research results show that students in the high and medium prior knowledge categories wholly and correctly prove each computational thinking stage. Students can present problems visually, explain the flow of solution ideas used, write down the steps in detail and precisely, and check all solutions and final conclusions. Students in the low prior knowledge category need to improve at the design and algorithm stages—students' errors in interpreting the problem abstractly so that there is some misinformation. As a result, the completion steps and wrong results are obtained at the algorithm stage. The research results can be used to determine learning strategies in the classroom so that computational thinking skills increase.